Coupling of FEM and EFGM with dynamic decomposition in 2D quasi-brittle crack growth analysis - Jaśkowiec, Jan; Cichoń, Czesław (Computer Assisted Methods in Engineering and Science, 2023)
In the paper three computational models for crack growth analysis in quasi-brittle materials in plane stress state are presented. These models have been worked out on the base of different methods of coupling the finite element method and the element free Galerkin method. Effectiveness of the methods of analysis are improved by the algorithm of dynamic domain decomposition into Ωh Ωe Ωhe parts. The usefulness of the methods in crack growth analysis has been confirmed in examples.